Chaotic asymmetric encryption process for data security. - Kamel Arrifin, Muhammad Rezal; Mohd Atan, Kamel Ariffin (2008)
Disclosed is a method and apparatus for a chaotic asymmetric encryption system that is based on a mathematically proven chaotic dynamical system, the ergodic property of chaotic maps, conventional Diffie-Hellman key exchange procedure, a modified Diffie-Hellman key exchange procedure and a public key which is any number that could be chosen from the interval 0,1.